Job insecurity and youth emancipation: a theoretical approach - Sascha O. Becker; Samuel Bentolila; Ana Fernandes; Andrea Ichino (Institute for the Study of Labor (IZA), 2005)
In this paper, we propose a theoretical model to study the effect of income insecurity of parents and offspring on the child's residential choice. Parents are partially altruistic toward their children and will provide financial help to an independent child when her income is low relative to the parents'. We show that first-order stochastic dominance (FOSD) shifts in the distribution of the child's future income (or her parents') will have ambiguous effects on the child's residential choice. The analysis identifies altruism as the source of ambiguity in the results. If parents are selfish or the joint income distribution of parents and child places no mass on the region where transfers are provided, a FOSD shift in the distribution of the child's (parents') future income will reduce (raise) the child's current income threshold for independence.
Keywords: D1; J1; J2; 330; altruism; emancipation; job security; option value